THE ROLE OF ACCOUNTING INFORMATION SYSTEMS IN ENHANCING FINANCIAL TRANSPARENCY AND FINANCIAL REPORTING FOR INSTITUTIONS (AN APPLIED STUDY IN THE SUMER COMMERCIAL BANK) - Shaymaa Abdulhusein Abdulkadhim Alisawi; Hayder kareem salim; Forat Sattar Hassoon (Scholar Express Journals, 2023)
The research aims to identify the nature of the accounting information system in banks and the most important automated means and technical tools used in its development. And suggesting some automated means and technical tools to develop the accounting information system in the Sumer Commercial Bank. The search was applied in the Sumer Commercial Bank for the financial year 2020 data. The research concluded that information technology is a tool for developing the accounting information system in banks and for improving the banking service through many tools, the most important of which are computers, automatic teller machines, plastic cards, electronic transfer of funds and banking operations using the Internet, as well as through telephone banking technology, office or home banking, digital money, e-mail and the branch. The use of automated and technical means in accounting information systems in banks supports operational processes and decision-making processes, as well as supporting the competitive advantage of the bank.
Keywords: processes; operational; decision